The relationship between obsessive beliefs and thought-control strategies in a clinical sample - Tolin, D; Worhunsky, P; Brady, R; Maltby, N (2007)
Previous research has linked obsessive-compulsive disorder (OCD) to maladaptive strategies of thought control, which in turn may elicit a paradoxical increase in the unwanted thought. One explanation for OCD patients' use of maladaptive thought control strategies is that they tend to overestimate the importance of their thoughts, or perceive a greater need to control them. The aim of the present study was to examine the relationship between obsessive beliefs and use of maladaptive thought control strategies in a sample of 77 OCD patients and 35 anxious control patients. Patients completed the Obsessive Beliefs Questionnaire-44 (OBQ-44) and the Thought Control Questionnaire (TCQ), as well as measures of trait anxiety and depression. Across the entire sample and for OCD patients only, when controlling for depression and trait anxiety, the TCQ Punishment scale correlated significantly with the OBQ-44 Importance/Control of Thoughts scale. Regression analyses indicated that beliefs about the Importance/Control of Thoughts accounted for the relationship between OCD and the use of Punishment as a thought control strategy. In addition to providing additional construct validation for the OBQ-44, the present data add to a growing body of research suggesting that OCD patients, believing their intrusive thoughts to be particularly important and perceiving a need to control them, overuse maladaptive thought control strategies; these strategies tend to "backfire" and trigger additional intrusive thoughts. © 2006 Springer Science+Business Media, Inc.